Structure–activity relationship of dendrimers engineered with twenty common amino acids in gene delivery. (1st January 2016) - Wang, Fei; Hu, Ke; Cheng, Yiyun
Graphical abstract: Abstract: Systematic explorations on the structure–activity relationship of surface-engineered dendrimers are essential to design high efficient and safe gene vectors. The chemical diversity of residues in naturally occurring amino acids allows us to generate a library of dendrimers with various surface properties. Here, we synthesized a total number of 40 dendrimers engineered with the twenty common amino acids and investigated their performances in gene delivery. The results show that gene transfection efficacy of the synthesized materials depends on both the type of amino acid and the conjugation ratio. Dendrimers engineered with cationic and hydrophobic amino acids possess relatively higher transfection efficacies. Engineering dendrimers with cationic amino acids such as arginine and lysine facilitates polyplex formation and cellular uptake, with histidine improves endosomal escape of the polyplexes, and with hydrophobic amino acids such as tyrosine and phenylalanine modulates the balance between hydrophobicity and hydrophilicity on dendrimer surface, which is beneficial for efficient cellular internalization. Dendrimers engineered with anionic or hydrophilic amino acids show limited transfection efficacy due to poor DNA binding capacity and/or limited cellular uptake. In the aspect of cytotoxicity, dendrimers engineered with arginine, lysine, tyrosine, phenylalanine and tryptophan show much higher cytotoxicity than other engineered dendrimers. These results are helpful for us to tailor the surface chemistry of dendrimers for efficient gene delivery. Statement of significance: Cationic polymers such as dendrimers were widely used as gene vectors but are limited by relatively low delivery efficacy and high toxicity. To achieve efficient and low toxic gene delivery, the polymers were modified with various ligands. However, these ligand-modified polymers in gene delivery are reported by independent researchers using different polymer scaffolds and cell lines. It is hard to provide structure-function information of these materials based on current knowledge and experience, which are essential for the design of ideal polymeric vectors for gene delivery. Here, we prepared a small library of amino acid-modified dendrimers, which is used as a screening pool to discover efficient gene vectors. The results obtained from this study, especially the structure–activity relationship of the screened materials are helpful for us to further design efficient and biocompatible polymers for gene delivery. This manuscript will appeal to a wide readership such as nanomaterial chemist, dendrimer chemist, biological chemist, pharmaceutical scientist, and biomedical researchers.